2021
DOI: 10.1111/bjhp.12552
|View full text |Cite
|
Sign up to set email alerts
|

Testing the content for a targeted age‐relevant intervention to promote cervical screening uptake in women aged 50–64 years

Abstract: Objectives. Low uptake of cervical screening in women in their 50s and 60s leaves them at elevated risk of cancer in older age. An age-targeted intervention could be an effective way to motivate older women to attend cervical screening. Our primary objective was to test the impact of different candidate messages on cervical screening intention strength. Design.A cross-sectional online survey with randomized exposure to different candidate messages.Methods. Women aged 50-64 years who were not intending to be sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 47 publications
3
6
1
Order By: Relevance
“…These findings suggest it is unlikely any single message can strengthen screening intentions for those with weak intentions to begin with and are similar to our previous study with women who did not intend to be screened (Marlow et al, 2021). The results of the present study contrast with cognitive dissonance theory (Festinger, 1957;Byskov Petersen et al, 2020) as we found no support that messages which were ineffective for women with negative intentions might work better for those who were more positively inclined towards screening (Marlow et al, 2021). There are important potential confounders associated with age, such as comorbidity, that could impact screening behaviour, which would be useful to measure in a future study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These findings suggest it is unlikely any single message can strengthen screening intentions for those with weak intentions to begin with and are similar to our previous study with women who did not intend to be screened (Marlow et al, 2021). The results of the present study contrast with cognitive dissonance theory (Festinger, 1957;Byskov Petersen et al, 2020) as we found no support that messages which were ineffective for women with negative intentions might work better for those who were more positively inclined towards screening (Marlow et al, 2021). There are important potential confounders associated with age, such as comorbidity, that could impact screening behaviour, which would be useful to measure in a future study.…”
Section: Discussionsupporting
confidence: 86%
“…There was no significant difference between the age-targeted messages and generic messages. This was similar to the findings of our previous study (Marlow et al, 2021), but inconsistent with the theory that targeted messages are more effective than generic ones (Kreuter and Wray, 2003). We also tested different message formats (negative or positive framing of the response efficacy message and short-and longterm time frames for the risk reduction message), and neither were more effective.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations